ASEAN-India Cooperation Project on ‘Extent of Transfer of Alien Invasive Organisms in South/Southeast Asia Region by Shipping’ - Arga Chandrasekar Anil; Koh Siang Tan (ASEAN Journal on Science and Technology for Development, 2018)
A brief background of events leading to the successful implementation of the first ASEAN-India project on marine sciences is provided. Coordinated by India and Singapore, the project, entitled ‘Extent of transfer of alien invasive organisms in South/Southeast Asia region by shipping’ served to develop regional cooperation and networks to address the issue of alien invasive organisms, provide training for ASEAN scientists, as well as obtain baseline information on pest species for port management in the light of IMO’s Ballast Water Management Convention. The project was completed with an international workshop held in Chiangmai, Thailand where some 29 presentations were made by ASEAN and Indian scientists based on the project activities. A total of 23 original articles are included in this volume. A proposal to implement a second phase of the project was formally submitted to the ASEAN-India Cooperation Fund in 2016.